JAGA IBU DARI ANEMIA DAN JAGA HIPERTENSI (JAMINI JATI) DI DESA SUKARAJA - Dainty Maternity; yuli yantina; Ratna Dewi Putri (Program Studi Kebidanan Fakultas Kedokteran, 2020)
masyarakat dengan penderita hipertensi dengan melakukan penanaman dan pemanfaatan tanaman obat keluarga (TOGA). Sasarannya adalah Kader Posyandu dan Ibu hamil dengan anemia, masyarakat dengan hipertensi serta seluruh masyarakat desa Sukaraja dalam meningkatkan kesejahteraan masyarakat. Penyuluhan dilakukan secara door to door dan kemudian dilakukan penanaman bibit pada salah satu lahan kosong di rumah warga di dusun 6 desa Sukaraja. Dalam pemeliharaan tanaman obat keluarga akan dilakukan oleh masyarakat dan mahasiswa selama masa pengabdian di desa tersebut. Dengan diadakannya kegiatan ini, dapat dijadikan sarana bagi masyarakat Desa Sukaraja, Pesawaran untuk menggunakan lahan kosong yang ada dihalaman rumah sebagai lahan tanaman obat keluarga.Kata Kunci: Anemia,hipertensi,jamini jatiABSTRACTThe case of anemia in pregnant women has many serious impacts / risks on the mother and the baby she is carrying. Hypertension is also a disease that is often experienced by the people of Sukaraja village and is one of the causes of death in Sukaraja village. The goal of the JAMINI JATI program is that it is hoped that it can help and provide benefits to the village of Sukaraja. This activity is a form of social activity that improves public health, especially pregnant women with anemia and people with hypertension by planting and using family medicinal plants (TOGA). The targets are Posyandu cadres and pregnant women with anemia, people with hypertension and all people in Sukaraja village in improving the welfare of the community. The counseling was carried out door to door and then seedlings were planted on one of the vacant land at the residents' houses in 6 hamlets of Sukaraja village. The community and students will carry out the maintenance of family medicinal plants during their service period in the village. By holding this activity, it can be used as a means for the people of Sukaraja Village, Pesawaran, to use the vacant land in the yard of the house as land for family medicinal plants.Keywords: Anemia, hypertension, jamini jati